Amorphous sulfur-rich CoSx nanodots as highly efficient cocatalyst to promote photocatalytic hydrogen evolution over TiO2. (5th December 2022) - Zhang, Rongguo; Gong, Kewei; Cao, Shunan; Du, Fuying
Abstract: In this work, amorphous cobalt sulfide with a sulfur-rich structure (sr-CoSx ) is developed as the cocatalyst for photocatalytic hydrogen evolution. Through a facile hydrothermal reaction, sr-CoSx nanodots are in situ grown on TiO2 to obtain a heterojunction photocatalyst (sr-CoSx /TiO2 ). The as-prepared photocatalyst exhibits remarkable improved hydrogen evolution performance compared with TiO2 . Under the irradiation of xenon lamp, the hydrogen evolution rate of sr-CoSx /TiO2 can reach 507 μmol h −1 g −1, which is about 121 times that of pristine TiO2, indicating that sr-CoSx is a highly efficient cocatalyst to promote hydrogen evolution on TiO2 . Moreover, sr-CoSx /TiO2 exhibits better performance than crystalline CoS2 or amorphous CoS modified TiO2, suggesting the important role of sulfur-rich structure and amorphous state in promoting the cocatalytic effect. Electrochemical and photoluminescence measurements show the most efficient carrier separation between sr-CoSx and TiO2, which also contributes to its high photocatalytic hydrogen evolution performance. Graphical abstract: Image 1 Highlights: Amorphous sulfur-rich CoSx nanodots are grown on TiO2 by hydrothermal method. The photocatalytic H2 evolution rate of sr-CoSx /TiO2 is 121 times that of TiO2 . The excellent activity is ascribed to the high S/Co ratio and the presence of Sx 2− . The facile electron transfer in sr-CoSx /TiO2 also contributes to the high activity.